Analisis Motivasi Kerja Pegawai Pada Kantor Camat Rasanae Barat Kota Bima - Fitriyaningsih Fitriyaningsih; Mistar Mistar (Journal of Business and Economics Research (JBE), 2020)
This research was conducted to analyze and explain how much the Employee Motivation at the Office of the Head of West Rasanae Sub-District, Bima City. In this research, the type of research used is descriptive. Nonprobability Sampling Technique is a sampling technique used. The number of samples used was 39 respondents, using the nonprobability sampling method. Based on the test results starting from the validity test, the reliability test states valid and reliability. The significance test (t test) states that "It is suspected that the Employee Work Motivation at the Office of the Head of West Rasanae Sub-district, Bima City is more than or equal to 75% of the expected criteria (already high)" can be proven or accepted.